Deletion of Swm2p selectively impairs trimethylation of snRNAs by trimethylguanosine synthase (Tgs1p) - Boon, Kum-Loong; Koš, Martin (FEBS letters, 2010)
MINT-7949540: swm2 (uniprotkb:P40342) physically interacts (MI:0915) with TGS1 (uniprotkb:Q12052) by tandem affinity purification (MI:0676)
Gesehen am 08.02.2023